Village Development Index and ICT Infrastructure in Tourism Region - Hidayat, AR. Rohman Taufiq; Prasetya, Yanuar Eka; Dinanti, Dian (Journal of Indonesian Tourism and Development Studies, 2019)
The tourism sector is one of the sectors that can be integrated with the village community empowerment, namely by utilizing the unique natural potential of the village. Tourism is one of the ways to improve the status of village development (Village Development Index/VDI). Tourism needs technological support to develop. Sukapura District is a strategic area for the development of tourism activities and has a low level of teledensity in Probolinggo Regency. This research aimed to examine the relationship of tourism region development related to ICT and village development in Sukapura District, Probolinggo Regency. This study used village development index analysis and literature review. The results of the analysis indicated that ICT infrastructure affected village development index which was related to the geographical conditions of the Sukapura area which was far from urban centers. Telephone service has been proposed as the main strategy to overcome geographical weaknesses which were related to its use in dealing with rural problems.Keywords: ICT Infrastructure, Tourism, Village Development Index.